Antiproliferative Effects Of The Orthosiphon Stamineus And Tualang Honey On Oral Squamous Cell Carcinoma And Human Osteosarcoma Cell Lines - Al-Ghashm, Abdulmlik (2010)
Cancer is the fourth leading cause of death in Malaysia with almost 30,000 people contracting the disease annually. One of the important research fields is the beneficial effects of plants and natural products as effective chemotherapeutic agents. Honey exhibits a broad spectrum of therapeutic properties including antibacterial, antifungal, anti-inflammatory and moderate anticancer effects. It contains many biologically active compounds such as caffeic acid, caffeic acid phenethyl ester and flavonoid glycones which have been proven to exhibit inhibitory effect on tumor cell proliferation. Orthosiphon stamineus (O. stamineus) or ‘misai kucing’ is a popular traditional folk medicine used as medicinal herb for many centuries. It has many medicinal properties such as antioxidant activity, antifungal activity, diuretic activity, antidiabetic activity, anti-inflammatory activity. No previous study has been done to evaluate the effect of Tualang honey and O. stamineus on oral squamous cell carcinoma (OSCC) and human osteosarcoma (HOS). This study was aimed to verify the antiproliferative activity for several concentrations of Tualang honey, O. stamineus and mixed concentrations of honey and O. stamineus on OSCC and HOS cell lines. Several doses of Tualang honey (1% - 20%), several concentrations of O. stamineus (100μg/ml to 1mg/ml) and several mixed solutions of both were applied on OSCC and HOS cell culture for 3, 6, 12, 24, 48 and 72 hours.